A database of installation monitoring and uplift load tests of round-shaft helical anchors in Brazil. (January 2023) - Da Silva, Bruno Oliveira; Tsuha, Cristina De Hollanda Cavalcanti; Dos Santos Filho, Joao Manoel Sampaio Mathias
Abstract: Helical anchors have been widely used during the last 15 years to support electrical transmission line towers in Brazil; however, the prediction of the uplift capacity of these anchors is still a very difficult task. Typically, costly and time-consuming static load tests complemented with torque–capacity correlations are used for the determination of anchor capacity. One reason for the inability of the existing design methods is the degree of soil disturbance during installation, which is variable according to the soil type, number of helices, anchor configuration, and quality of installation. Therefore, an extensive database of field load tests and installation monitoring of helical foundations in different Brazilian sites would be valuable to guide the engineers for a better and optimum design, reducing project cost. The current paper presents a helical anchor database that includes data of soil characterization, anchor geometry, installation torque and load–displacement response of 107 anchor cases in 40 different sites in Brazil. Additionally, an analysis of the data presented here indicated that the torque-correlation method, used frequently for the quality control of helical anchors, needs to be improved by considering the influence of parameters such as relative embedment depth and soil type. Moreover, this database can contribute to a better understanding of helical anchor behaviour and be used for: (i) calibration of uplift capacity estimation methods and of resistance factors for ULS and SLS design, (ii) development of torque–capacity correlation models, (iii) correlations between ultimate helix bearing pressure and SPT blow count; (iv) characterization of the uncertainties of design methods; (v) improvement of numerical models; etc.